Characterization and corrosion behavior of biodegradable Mg-Ca-Zn implant alloys - Yahya, Mohd. Yazid (2011)
In the present study binary Mg-xCa (x=0.5 and 1.25wt.%) and ternary Mg-1Ca-xZn (x=0.5 and 1.5wt.%) alloys are produced by casting the molten metal in a metal die at a temperature of 740°C. The microstructure analysis of the Mg-Ca and Mg-Ca-Zn alloys were studied by OM, SEM and EDX. The corrosion behavior of alloys was evaluated via potentiodynamic polarization test in Kokubo solution. The result exhibited that the grain size decrease with rising Ca content in Mg-Ca alloys and degree of grain size reduction further decreased by adding Zn to Mg-1Ca-Zn alloys. The microstructure of Mg-Ca alloys were constituted of primary Mg and lamellar eutectic (α-Mg+Mg 2Ca) phase, Whilst Mg-1Ca-Zn alloys were composed of primary Mg and eutectic (α-Mg+Mg 2Ca+Ca 2Mg 6Zn 3) phases. In addition with increasing Ca and Zn the amount of Mg 2Ca and Ca 2Mg 6Zn 3 increased respectively in grain boundaries. Electrochemical test shows that the addition of Zn leads to improve corrosion resistance of the Mg-1Ca-Zn alloys as a result of the formation of Ca 2Mg 6Zn 3 phase, whilst the addition of more than 0.5 wt% Ca to Mg-Ca alloys result in decrease corrosion resistance due to the formation Mg 2Ca.